Energy Management – State and Prospects of Development in Ukraine - Yushchyshyna, Larysa Oleksiivna (Lubelska Akademia WSEI, 2024)
The article is dedicated to the research of the current state and development prospects of energy management in Ukraine, whose energy system has been under massive attack by the Russian Federation for an extended period. It analyzes the damage inflicted on Ukraine's energy sector by the Russian full-scale invasion. It is determined that, under current conditions, Ukraine's energy system cannot function as stably as it did before the war. The role, significance, and tasks of energy management in the recovery and development of the country's energy sector are elucidated. The article justifies a step-by-step approach to forming an energy management system across three levels of development. It examines the current state of energy management in Ukrainian cities and amalgamated territorial communities. The article highlights the challenges and opportunities organizations face when implementing energy management systems. It offers suggestions for potential solutions to the problems identified in the analysis. The importance of strategic investments in renewable energy and international cooperation for supporting energy security and economic growth in Ukraine is emphasized. The necessity of reforming energy policy to adapt to new challenges, which will contribute to sustainable infrastructure development and strengthen partnerships with international donors and investors, is underscored.
Keywords: energy management; energy management system; energy monitoring; energy efficiency